Low-dimensional pseudoboehmite structures for microorganism adsorption; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Fomenko A. N. Alla Nikolaevna; Tikhonova I. N. Irina; Bakina O. V. Olga Vladimirovna; Glazkova E. A. Elena Alekseevna; Svarovskaya N. V. Natalia Valentinovna; Lozhkomoev A. S. Aleksandr Sergeevich; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen